1980
DOI: 10.1515/jpme.1980.8.4.183
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic changes of the pre-ejection period of the human fetal heart during umbilical cord complications

Abstract: l IntroductionA differential analysis of the cardiotocogram allows conclusions äs to the functional state of the fetus. However, the interpretations of changes in the heart rate depend to a large extent on the experience of the examiner because of the poorly defined deliminations of specific pattems of heart rate changes. New techniques enable the recording of the pre-ejection period (PEP) of the human fetal heart; i.e., the time between ventricular excitation and aortic pressure rise, continuously parallel wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1982
1982
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…and one effect of this seems to be lengthening of PEP. Thus, Organ et al (1974) found prolonged PEP in seven fetuses, in three of which the FHR pattern of variable decelerations suggested umbilical cord compression, while Bartling et al (1980) recorded prolonged PEP in 15 of 3s fetuses with nuchal cord entanglement. We now add eight further examples of lengthened PEP in association with variable FHR decelerations, in four of which tight cord entanglement was confirmed at birth.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…and one effect of this seems to be lengthening of PEP. Thus, Organ et al (1974) found prolonged PEP in seven fetuses, in three of which the FHR pattern of variable decelerations suggested umbilical cord compression, while Bartling et al (1980) recorded prolonged PEP in 15 of 3s fetuses with nuchal cord entanglement. We now add eight further examples of lengthened PEP in association with variable FHR decelerations, in four of which tight cord entanglement was confirmed at birth.…”
Section: Discussionmentioning
confidence: 90%
“…In addition to animal studies measurement of fetal cardiac electromechanical intervals (FCEMI) in the human has been reported from several centres (Organ el al. 1973a;Murata & Martin 1974;Bartling et al 1980) as well as by our team (Robinson et al 1978;Adam et al 1980).…”
mentioning
confidence: 77%
“…The fetal systolic time intervals have been analysed by several research groups in the past 3–6 . The fetal pre‐ejection period has been studied the most extensively 7–11 . The fetal pre‐ejection period was defined as the interval between the onset of QRS complex of the fetal electrocardiogram and the beginning of ventricular ejection, timed as the opening of the aortic valve.…”
Section: Introductionmentioning
confidence: 99%
“…The systolic time intervals of the fetal cardiac cycle have been analyzed by several authors in the past [4][5][6][7] . The fetal PEP was defined as the interval between the onset of the QRS complex (electrical activity on the fetal electrocardiogram (ECG) relating to ventricular contraction) and the beginning of ventricular ejection, timed as the opening of the aortic valve.…”
Section: Introductionmentioning
confidence: 99%